Role-Playing Between Environmental Pollutants and Human Gut Microbiota: A Complex Bidirectional Interaction - Giambò, Federica; Costa, Chiara; Teodoro, Michele; Fenga, Concettina (Frontiers in Medicine, 2022)
There is growing interest in the involvement of chemicals exposure in the development and the progression of several health disturbs such as obesity, diabetes, tumor and disruption of the immune and reproductive homeostasis. Moreover, the gut microbiota is the first responder against the toxic properties of chemicals with a bidirectional relation, underlining the toxicological significance of this mutual interplay. Furthermore, environmental chemicals have been demonstrated to change the composition, the biodiversity and the metabolic pathways of the gastrointestinal bacteria, which may play an important role in tailoring an individual’s microbiotype. In this review, we aimed to discuss the latest updates in figuring out environmental chemicals-microbiota interactions, the distinctiveness of microbial community in order to adopt personalized preventive strategies to improve risk assessment for more susceptible workers.